Antibacterial Activity of Ethanolic Extract of Trisamo Against Diarrheal Pathogen - Asae, Asma; Meemak, Puwadon; Poonthananiwatkul, Benjawan; Hemtrakoonwong, Rosenanee; Sama-ae, Suhaila (Princess of Naradhiwas University Journal, 2019)
The objective of this research was to study the antibacterial activities of ethanolic extract of Trisamo against diarrhea caused bacteria (Escherichia coli and Salmonella spp.). Trisamo extract included Terminalia chebula Retz., Terminalia arjuna Roxb. and Terminalia bellirica (Gaertn.) Roxb. was tested on their antimicrobial activities by using agar disc diffusion method. For evaluating Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC), macrodilution method was applied in this study and three experiments were repeated for each test to get an average. The results of this study showed that yield percent of crude ethanolic extract was 19.09. The average of inhibition zone for Escherichia coli (E. coli) and Salmonella spp. from Trisamo extract presented as 9.34 ? 0.58 mm. and 9.00 ? 0.00 mm, respectively. MIC for E. coli and Salmonella spp. were 256 ?g/ml and 512 ?g/ml and MBC for both were > 1024 ?g/ml respectively. In comparison MBC of Trisamo extract with norfloxacin as standard, MBC of norfloxacin demonstrated as 16 ?g/ml that was more effective than Trisamo extract as 16 times.